The Cause of Trichinosis and its Prevention Through Safe Food Handling Practices - Alina Balaguero; Keith R. Schneider (EDIS)
FSHN10-05, a 5-page fact sheet by Alina Balaguero and Keith R. Schneider, discusses Trichinosis, an infection caused by the foodborne pathogen Trichinella, and provides information on preventing the infection, recognizing symptoms, and receiving treatment. Includes references. Published by the UF Department of Food Science and Human Nutrition, June 2010.